Pyrolysis of waste fiber reinforced polyurethane-poly (meth) acrylate composites for recovery of recoverable materials
Through industrial-scale pyrolysis methods, fiber-reinforced polyurethane-poly(meth)acrylate composite materials are decomposed, which solves the recycling and utilization problems, and achieves the stability of efficient recycling of polyurethane materials and fibers, reducing environmental pollution and resource waste.
Patent Information
- Application Number
- CN202380076486.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-30
- Filing Date
- 2023-11-24
- Publication Date
- 2025-08-08
AI Technical Summary
The prior art has failed to effectively recycle and utilize fiber-reinforced polyurethane-poly(meth)acrylate composite materials, resulting in landfill or incineration, causing environmental pollution and waste of resources, and traditional pyrolysis methods are not suitable for such materials.
An industrial-scale pyrolysis method is adopted to optimize the recovery process of the catalyst and the catalyst and the recovery process of the catalyst and the catalyst and the reinforcing material by decomposing the fiber-reinforced polyurethane-poly(meth)acrylate composite at 350°C to 700°C.
Improve the selectivity and efficiency of recyclables, recover a large number of aromatic amine compounds that can be reused for the production of polyurethane materials, and recover fiber materials with mechanical strength, reducing environmental pollution and resource waste.
Smart Images

Figure GDA0005428317520000121 
Figure GDA0005428317520000191 
Figure GDA0005428317520000212
Abstract
Description
[0001] The present invention relates to a pyrolysis method for thermally recycling waste fiber-reinforced polyurethane-poly(meth)acrylate composite materials, and also relates to a composition comprising the waste fiber-reinforced polyurethane-poly(meth)acrylate composite materials and at least one catalyst for the above method, as well as use of the catalyst for thermally recycling waste fiber-reinforced polyurethane-poly(meth)acrylate composite materials.
[0002] European Patent EP 3129422 B1 discloses that fiber-reinforced polyurethane-poly(meth)acrylate composites can be used to manufacture products such as wind turbine blades, wind turbine nacelle shells, ship propeller blades, ship hulls, automotive interior and exterior trim, automotive bodies, radar antenna covers, mechanical structural parts, and decorative and structural parts for buildings and bridges. To meet the aforementioned product characteristics, the composite materials must provide excellent mechanical strength and weather resistance.
[0003] In particular, there are no reports on methods for recycling waste fiber-reinforced polyurethane-poly(meth)acrylate composites. Currently, waste fiber-reinforced polyurethane-poly(meth)acrylate composites are likely to be landfilled or incinerated. Incineration emits CO₂, exacerbating global warming. Landfill waste has a low density but a large volume, potentially polluting rivers and oceans.
[0004] Therefore, it is necessary to develop a recycling method to solve the disposal problem and recover resources from waste materials, thereby saving fossil resources.
[0005] Known methods for recycling plastic waste can be broadly divided into three categories:
[0006] (1) Mechanical recycling: Plastic waste is melted and recycled. This method is not suitable for fiber-reinforced polyurethane-poly(meth)acrylate composites.
[0007] (2) Chemical and thermochemical recycling: According to this method, plastic waste will be depolymerized or broken down into smaller molecules to recover useful chemical raw materials.
[0008] (3) Heat recovery, in which plastic waste will be mainly converted into waste gas and heat energy.
[0009] Chemical raw materials recovered as a product of thermochemical recycling can be used to synthesize new fiber-reinforced materials.
[0010] Thermochemical recycling, also known as pyrolysis, is commonly used to recycle packaging waste to recover pyrolysis oil, which can be used as recycled naphtha and added as supplementary feedstock to the cracking unit of a conventional crude oil refinery.
[0011] In order to recover polymer precursors of recycled waste fiber reinforcement materials other than the above-mentioned recycled naphtha, the general pyrolysis process must be modified.
[0012] et al. (J. of Reinforced Plastics and Composites 31(17); 2012; 1136-1142) reported a method for recycling glass fibers from composite materials of used wind turbine blades using microwave pyrolysis. The material of the wind turbine blades comprises glass fibers embedded in a polyester resin.
[0013] Patent application WO 2015 / 162505 A1 discloses a method for pyrolyzing glass fiber-reinforced plastic waste to recover organic and inorganic components, enabling their advantageous reuse as raw materials for the manufacture of new articles. However, the pyrolysis of fiber-reinforced polyurethane-poly(meth)acrylate composites is not mentioned.
[0014] Patent application WO 2021 / 068083 A1 relates to the recycling of fiber-reinforced polymer materials to recover reusable intact fibers and powdered polymer resins. However, it does not mention the pyrolysis of fiber-reinforced polyurethane-poly(meth)acrylate composites.
[0015] Furthermore, it has been reported that if catalysts or additives are used during the pyrolysis process, the operating temperature can be lowered, the reaction time can be reduced, the degradation efficiency can be improved, and the product distribution can be restricted, leading to a more efficient process.
[0016] M. Blazsó et al. (J. Chromatogr. A 1271 (2013) 217-220) revealed that when a basic NH4Y zeolite is used as a catalyst, the primary product of the thermal decomposition of polyurethane materials containing a polyol component is THF from the polyol component. Two other products, aniline and 4-methylaniline, can also be readily identified from the catalytic decomposition of diphenylmethane diisocyanate (MDI).
[0017] To achieve industrial-scale pyrolysis of large quantities of fiber-reinforced polyurethane-poly(meth)acrylate composites, new pyrolysis processes with higher selectivity are needed to reduce the amount of by-products and increase the amount of recyclables that can be reused. The resin of the fiber-reinforced polyurethane-poly(meth)acrylate composite should be converted into pyrolysis products that contain a high yield of recyclables that can be used to synthesize polyurethanes and poly(meth)acrylates, preferably aromatic amines as recyclables, such as aniline, toluidine, methylenedianiline (mMDA), or polymeric methylenedianiline (pMDA).
[0018] In addition, the fibers of fiber-reinforced polyurethane-poly(meth)acrylate composites should be recovered in a reusable state, in particular for the production of fiber-reinforced materials or non-woven glass mats.
[0019] Thus, one aspect of the present invention is to provide an industrial-scale process for the pyrolysis of fiber-reinforced polyurethane-poly(meth)acrylate composites, in particular from scrap wind turbine blades.
[0020] Another aspect of the present invention is to provide a composition as a raw material for the industrial-scale pyrolysis of fiber-reinforced polyurethane-poly(meth)acrylate composites, which improves the selectivity of the pyrolysis process and leads to the recovery of large amounts of recyclables that can be reused in the production of polyurethane materials, preferably in an amount greater than 40% by weight relative to the total weight of the initially introduced resin components of the fiber-reinforced polyurethane-poly(meth)acrylate composites.
[0021] Another aspect of the present invention is to recover fibers from fiber-reinforced polyurethane-poly(meth)acrylate composites, which as recyclables have sufficient stability and mechanical strength to be reused as fibers for fiber-reinforced composites.
[0022] At least one of the above aspects can be achieved by a pyrolysis method for waste fiber reinforced polyurethane-poly (meth) acrylate composite material, the method comprising at least the following steps:
[0023] (a) introducing a feedstock comprising at least one fiber-reinforced polyurethane-poly(meth)acrylate composite waste material into a reactor,
[0024] The fiber-reinforced polyurethane-poly(meth)acrylate composite material in the waste is obtained from at least one reinforcing material and at least one polyurethane-poly(meth)acrylate reactive composition, wherein the polyurethane-poly(meth)acrylate reactive composition comprises:
[0025] A) an isocyanate component comprising one or more organic polyisocyanates;
[0026] B) an isocyanate-reactive component comprising:
[0027] B1) one or more (meth)acrylate monomers containing at least one hydroxyl functional group;
[0028] B2) one or more organic polyols;
[0029] C) a free radical reaction initiator, and
[0030] wherein the polyurethane-poly(meth)acrylate resin is obtained by reacting the components, preferably by a one-pot process; and
[0031] (b) decomposing the polyurethane-poly(meth)acrylate resin in the introduced fiber-reinforced polyurethane-poly(meth)acrylate composite waste at a temperature of 350° C. to 700° C. in the presence of at least one catalyst capable of affecting thermal decomposition of the waste, to obtain at least a gaseous pyrolysis product and a pyrolysis residue, the pyrolysis residue containing at least the separated reinforcing material as a solid, wherein
[0032] (i) during the decomposition process, the amount of oxygen in the reactor is at most 2.0% by volume of the total volume of the gas phase in the reactor, and
[0033] (ii) during said decomposition process, removing the pyrolysate from the reactor, and
[0034] (iii) removing the pyrolysis residue from the reactor; and
[0035] (c) cooling the removed pyrolysate to below 350° C. to obtain a pyrolysate selected from a pyrolysate condensate, a sublimed pyrolysate, or a mixture thereof; and
[0036] (d) preferably recovering the reinforcing material and catalyst from the pyrolysis residue.
[0037] "Feedstock" refers to the totality of materials introduced into the reactor for pyrolysis, where they are thermally treated in the absence of oxygen or in the presence of a small amount of oxygen. The feedstock is preferably solid before being introduced into the reactor.
[0038] The term "(meth)acrylate" refers to a group of compounds consisting of acrylic acid and its derivatives, methacrylic acid and its derivatives.
[0039] The term "poly(meth)acrylate" refers to a group of polymers or copolymers prepared from at least one or more (meth)acrylate monomers.
[0040] "Pyrolysate" refers to all products formed from pyrolysis which are in the gas phase of the reactor under the conditions of step (b).
[0041] "Pyrolysis residue" is the total amount of material formed by pyrolysis and other residues of the starting material which is not in the gas phase of the reactor under the conditions of step (b). A preferred embodiment of the process according to the invention is characterized in that the pyrolysis residue is a solid.
[0042] "Pyrolysis products" refers to the total amount of products in the pyrolysate that accumulates by condensation and / or resublimation upon cooling the pyrolysate according to step (c). Liquid pyrolysis products are also referred to as pyrolysis oil.
[0043] Unless the context clearly defines otherwise, a substance (e.g., a material, a feedstock, a pyrolysis product, a pyrolysis residue) is a "liquid" if it is liquid at 20°C and 1013 mbar. Unless the context clearly defines otherwise, a substance (e.g., a material, a feedstock, a pyrolysis product, a pyrolysis residue) is a "solid" if it is solid at 20°C and 1013 mbar. Unless the context clearly defines otherwise, a substance (e.g., a material, a feedstock, a pyrolysis product, a pyrolysis residue) is a "gas" if it is gaseous at 20°C and 1013 mbar.
[0044] A substance is "organic" if its chemical structure contains at least one covalent carbon-hydrogen bond.
[0045] The average molecular weights Mw given for polymers or polymeric components in the context of this application are—unless expressly stated otherwise—always weight-average molecular weights Mw, which can generally be determined by gel permeation chromatography using an RI detector, the measurement being carried out against an external standard.
[0046] "Reactor" refers to the volume in which a chemical conversion (e.g., thermal decomposition of a substance in a pyrolysis material) is carried out. For pyrolysis, for example, this may be the volume of a heated container in which the pyrolysis material is placed.
[0047] According to a preferred embodiment of the method, it is advantageous to introduce the pyrolysis material into a reactor which is characterized in that it is selected from a continuous stirred tank reactor (CSTR), a fixed bed reactor, a fluidized bed reactor, a screw reactor, a screw conveyor reactor, an entrained flow bed reactor, a rotary tubular reactor, a paddle reactor. In particular, a reactor into which the pyrolysis material can be introduced continuously is preferably suitable and is preferably selected from a rotary tubular reactor, a continuous stirred tank reactor (CSTR), a fixed bed reactor (in particular a continuous bed exchanger (vertical reactor) with an internal heat exchanger, preferably with internal heat exchange tubes), a screw reactor, a screw conveyor reactor, an entrained flow bed reactor, a rotary tubular reactor or a fluidized bed reactor. A particularly preferred reactor in one embodiment of the method is selected from a screw reactor, a rotary kiln or a fluidized bed. Other preferred reactors for the method of the invention and embodiments thereof are described below (see below).
[0048] According to the present invention, the raw materials introduced into the reactor include fiber-reinforced polyurethane-poly(meth)acrylate composite waste and, in some cases, a catalyst. In one embodiment of the process according to the invention, the pyrolysis material comprises the waste in an amount of 10.0 to 80.0% by weight, more preferably 30.0 to 70.0% by weight, in each case based on the total weight of the pyrolysis material.
[0049] It has been found that it is advantageous if the composite waste materials in the feedstock are introduced into the reactor in the form of solid particles. The optimal particle size of the particles depends on the choice of the feed system for the pyrolysis reactor. It has been found that it is advantageous to introduce the waste materials in the form of particles having a particle size of 10 cm to 1 mm.
[0050] The fiber-reinforced polyurethane-poly(meth)acrylate composite scrap can be part of a scrap product selected from wind turbine blades, wind turbine nacelle shells, ship propeller blades, ship hulls, automotive interior and exterior trim, automotive bodies, radomes, mechanical structural parts, and decorative and structural parts for buildings and bridges. The scrap product is composed of a plurality of different components, at least one of which contains fiber-reinforced polyurethane-poly(meth)acrylate composite scrap, which is contained in the raw material.
[0051] Preferably, the scrapped product is selected from wind turbine blades. The main features of a typical wind turbine blade structure and the materials used to manufacture wind turbine blades can be found in the review article Mishnaevsky et al., Materials, 10(11), 2017, 1285 (DOI: 10.3390 / ma10111285): A wind turbine blade consists of two faces (suction face and pressure face) which are connected together and reinforced by one or more integral (shear-resistant) webs connecting the upper and lower parts of the blade shell or by box beams (box beams with shell fairings). The blade structure consists of a plurality of elements, namely the shear webs, the load-bearing beams, the leading and trailing edges and the aerodynamic shells. The aerodynamic shells of the two faces comprise a fiber-reinforced composite material. The shells are bonded together. Vacuum assisted resin transfer molding (VARTM) is the most commonly used manufacturing method for manufacturing wind turbine rotor blades. According to VARTM, multiple layers of dry fiber fabric (with nearly all unidirectional fibers aligned along the length of the blade) are placed on a mold part and placed together with polymer foam or, for sandwich structures (for the aerodynamic shell), balsa wood. The fabric is then covered with a vacuum bag and sealed. After applying a vacuum, a resin (e.g., a polyurethane-poly(meth)acrylate resin) flows in and wets the fibers. After infusion, the resin cures at room temperature. In most cases, wind turbine rotor blades are made of large components, for example, two aerodynamic shells with a load-bearing box (spar) or an inner web, which are then bonded together with an adhesive.
[0052] End-of-life products are often made of a variety of materials. Recycling of end-of-life products, such as wind turbine blades, could be facilitated by reducing the diversity of materials used to manufacture them. At a minimum, the chemical composition of the materials used should enhance the recyclability of the product. Wind turbine blades are made of a variety of materials, such as wood, foam, reinforcements, resins, and adhesives. To facilitate recycling, it might be advantageous to provide alternatives to the foam or wood mentioned above, which are made from compounds with a chemical composition similar to that of the resins used in fiber-reinforced composite materials.
[0053] The polyurethane-poly(meth)acrylate composite material contained in the raw materials of the present invention comprises a polyurethane-poly(meth)acrylate resin and a reinforcing material prepared from a polyurethane-poly(meth)acrylate reactive composition, wherein the polyurethane-poly(meth)acrylate reactive composition comprises:
[0054] A) an isocyanate component comprising one or more organic polyisocyanates;
[0055] B) an isocyanate-reactive component comprising:
[0056] B1) one or more (meth)acrylate monomers containing at least one hydroxyl functional group (hereinafter referred to as "hydroxy (meth)acrylate monomers")
[0057] B2) one or more organic polyols;
[0058] C) a free radical reaction initiator, and
[0059] The polyurethane-poly(meth)acrylate resin is prepared by mixing component B) with components A) and C) and reacting them, for example preferably by a one-pot process.
[0060] For the purposes of this application, the term "polyisocyanate" is used for organic compounds containing two or more isocyanate groups (-N=C=O).
[0061] As used herein, the term "functionality" or "f" refers to the average functionality (number of active hydrogen atoms per molecule) of a polyol or polyol mixture, assuming it is the same as the average functionality (number of active hydrogen atoms per molecule) of the starting compounds used in the preparation of the polyol.
[0062] For isocyanates, the term f(NCO) refers to the average number of reactive isocyanate groups in the respective compound.
[0063] With respect to a compound, the term f(olefin) refers to the average number of reactive olefin groups in the respective compound.
[0064] For the purposes of this application, the term "one-pot process" is used to refer to a process in which the reaction of components A), B1) and B2) is initiated in the presence of C), and the reaction conditions are selected so that the polyurethane formation and the free-radical olefin polymerization proceed simultaneously or at least partially in parallel. Typically, once all components are mixed, the polyurethane addition reaction is initiated, followed by the free-radical polymerization reaction at elevated temperatures (depending on the thermal instability of initiator C). Both reactions reach their maximum conversion simultaneously.
[0065] As polyisocyanate component A), customary aliphatic, cycloaliphatic and, in particular, aromatic diisocyanates and / or polyisocyanates can be used. Examples of suitable polyisocyanates of this type are 1,4-butylene diisocyanate, 1,5-pentylene diisocyanate, 1,6-hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), 2,2,4- and / or 2,4,4-trimethylhexamethylene diisocyanate, bis(4,4'-isocyanatocyclohexyl)methane or mixtures thereof with other isomers, 1,4-cyclohexyl diisocyanate, 1,4-phenylenediisocyanate, 2,4- and / or 2,6- Toluene diisocyanate (TDI), 1,5-naphthalene diisocyanate, 2,2'- and / or 2,4'- and / or 4,4'-diphenylmethane diisocyanate (monomeric MDI, mMDI), higher homologs (oligomeric MDI), mixtures of monomeric and oligomeric MDI (polymeric MDI, pMDI), 1,3- and / or 1,4-bis-(2-isocyanatoprop-2-yl)benzene (TMXDI), 1,3-bis-(isocyanatomethyl)benzene (XDI). Preference is given to using diphenylmethane diisocyanate (MDI) as the isocyanate, in particular a mixture of diphenylmethane diisocyanate and polyphenylenepolymethylene polyisocyanate (pMDI). The preferred monomer content of the mixture of diphenylmethane diisocyanate and polyphenylenepolymethylene polyisocyanate (pMDI) is 10 to 100% by weight, preferably 20 to 80% by weight, particularly preferably 30 to 60% by weight. The NCO content of the polyisocyanate used (measured according to DIN EN ISO 14896:2009-07) is preferably greater than 23% by weight, more preferably greater than 26% by weight, and particularly preferably greater than 30% by weight. The functionality of the isocyanate is preferably 2.0-3.5, more preferably 2.1-2.9. The viscosity of the isocyanate is preferably ≤750 mPa*s (at 25°C), more preferably ≤500 mPa*s (at 25°C), and particularly preferably ≤300 mPa*s (at 25°C) [measured according to DIN 53019-1:2008-09]. When used in the present invention, the organic polyisocyanate may comprise dimers, trimers, tetramers or pentamers of isocyanates and / or combinations thereof.
[0066] Modified, blocked and prepolymerized isocyanates, which can be prepared, for example, by reacting an excess of an organic polyisocyanate or a mixture of organic polyisocyanates with a polyol compound, can also be used as isocyanate component A). The compounds and their preparation are described in the technical literature.
[0067] The isocyanate-reactive component B) further comprises hydroxy(meth)acrylate monomers B1).
[0068] In a preferred embodiment, the hydroxyl (meth)acrylate monomer has a hydroxyl value of 150-700 mg KOH / g, more preferably 220-600 mg KOH / g, more preferably 300-500 mg KOH / g, the average hydroxyl functionality of B1) is 1-3, more preferably 1-2, more preferably 1, and the average alkenyl functionality of B1) is 1-3, more preferably 1-2, more preferably 1. Particularly preferably, B1) is selected from hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and combinations thereof.
[0069] B1) can be prepared by conventional methods in the art, for example, by esterification reaction of (meth)acrylic anhydride, (meth)acrylic acid or (meth)acryloyl halide with HO-(R2O)nH.
[0070] The one or more organic polyols B2) are preferably selected from polyether polyols, polyester polyols, polyether ester polyols, polymer polyols, polycarbonate polyols, polyether carbonate polyols and combinations thereof. Polyether polyols and / or polyester polyols are particularly preferably used in the polyol formulation. It is particularly preferred to use polyether polyols as the sole polyol.
[0071] Such polyols are described, for example, in Ionescu, “Chemistry and Technology of Polyols for Polyurethanes”, Rapra Technology Limited, Shawbury 2005, p. 31 ff. (Chapter 3: The General Characteristics of Oligo-Polyols), p. 55 ff. (Chapter 4: Oligo-polyols for Elastic Polyurethanes), p. 263 ff. (Chapter 8: Polyester Polyols for Elastic Polyurethanes) and in particular p. 32 ff. (Chapter 13: Polyether Polyols for Rigid Polyurethane Foams) and p. 419 ff. (Chapter 16: Polyester Polyols for Rigid Polyurethane Foams).
[0072] In a preferred embodiment, the polyol has a hydroxyl number of 150 to 700 mg KOH / g, more preferably 220 to 600 mg KOH / g, and the average functionality of the polyol in B2) is 1.5 to 4.5, more preferably 1.9 to 3.2, and still more preferably 2.2 to 2.8. The numerical values for hydroxyl numbers (herein referred to as "OH numbers") given in this application are measured in accordance with DIN EN ISO 53240 Part 2 (November 2007).
[0073] As component B2), one or more polyhydroxy polyethers ("polyether polyols") are preferably used. These can be prepared in a manner known to those skilled in the art by polyaddition of alkylene oxides (e.g., propylene oxide and / or ethylene oxide) onto polyfunctional starter compounds in the presence of catalysts. The polyhydroxy polyethers are preferably prepared from the starter compounds and one or more alkylene oxides (e.g., ethylene oxide, butylene oxide, and / or propylene oxide). Preferred starter compounds are molecules having 2 to 8 hydroxyl groups per molecule, such as water, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, 1,4-butanediol, 1,6-butanediol, bisphenol A, glycerol, trimethylolpropane, pentaerythritol, sorbitol, and sucrose. Particularly preferred starting materials are 1,2- and 1,3-propylene glycol, diethylene glycol, sorbitol, glycerol, trimethylolpropane, sucrose, and mixtures of the aforementioned products.
[0074] Particular preference is given to polyether polyols based on propylene oxide, in particular propylene oxide polyethers having a functionality of 2 to 3. For these polyethers, 1,2-propylene glycol, glycerol and / or trimethylolpropane are particularly preferred as starter compounds.
[0075] Polyester polyol is the polyol containing ester group, such as castor oil or polyhydroxy polyester, such as can be obtained by the polycondensation of simple polyol of excessive above-mentioned type and preferably dicarboxylic acid or its anhydride.Described dicarboxylic acid is preferably but not limited to the aliphatic carboxylic acid with 2-12 carbon atoms, preferably but not limited to succinic acid, malonic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecyl carboxylic acid, maleic acid, fumaric acid, phthalic acid, isophthalic acid, terephthalic acid, or its combination.The anhydride of corresponding acid can also or alternatively be used as reactant.In addition, monoacid, such as benzoic acid or alkanoic acid, and / or the acid prepared by hydroxycarboxylic acid (such as hydroxycaproic acid, hydroxybutyric acid, hydroxystearic acid, hydroxydecanoic acid etc.) can also be used.Described polyester polyol also comprises by lactone (such as ε-caprolactone, butyrolactone etc.) or with the polyester polyol prepared by this lactone.
[0076] Examples of polyols that react with acids are ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, dipropylene glycol, 1,3-methylpropanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,10-decanediol, glycerol, trimethylolpropane, or combinations thereof. Monohydric alcohols can also be used.
[0077] Bio-based compounds and their derivatives can also be used to produce polyester polyols, such as vegetable oils, vegetable oil polyols or modified products thereof. Vegetable oils are compounds made from unsaturated fatty acids and glycerol, or oils extracted from, for example, plant fruits or seeds. Examples include, but are not limited to, castor oil, polyhydroxy fatty acids, ricinoleic acid, grapeseed oil, pumpkin seed oil, palm oil, olive oil, avocado oil, coconut oil, palm kernel oil, cocoa butter, cottonseed oil, pumpkin seed oil, corn oil, sunflower seed oil, wheat germ oil, sesame oil, hemp oil, thistle oil. Oil), linseed oil, soybean oil, peanut oil, lupine oil, borage oil, mustard oil, jatropha oil, walnut oil, jojoba oil, lecithin (e.g., based on soybean), evening primrose oil, wild rose oil, peanut oil, walnut oil, hazelnut oil, rapeseed oil, and castor oil, fatty acids, hydroxyl-modified fatty acids, polyhydroxy fatty acids, and epoxidized fatty acids and fatty acid esters, for example, based on myristic acid, palmitoleic acid, oleic acid, trans-vaccenic acid, petroselinic acid, gadoleic acid, erucic acid, nervonic acid, linoleic acid, α- and γ-linoleic acid, stearidonic acid, arachidonic acid, eicosapentaenoic acid, docosapentaene, and cervicic acid. It is also advantageous to use mixtures of such biobased acids with other carboxylic acids (e.g., phthalic acid). Hydroxyl groups can be further introduced into the starting materials of the vegetable oil polyols by methods such as cleavage, oxidation, or transesterification, and then the vegetable oil polyols can be prepared using methods for preparing organic polyols known to those skilled in the art. When bio-based polyols are used, esters prepared from ricinoic acid and polyfunctional alcohols are particularly preferred.
[0078] The polyester polyols used in compound B2) alone or in a mixture with, for example, polyether polyols preferably have a molecular weight of 200-3000 g / mol and a functionality of 2-6, preferably 2-4, more preferably 2-3.
[0079] Other polyols can also be used in component B2), preferably in the form of a mixture with the abovementioned polyether polyols and / or polyester polyols.
[0080] Polycarbonate polyols are polycarbonates containing hydroxyl groups, such as polycarbonate diols. They are prepared by reacting carbonic acid derivatives (such as diphenyl carbonate, dimethyl carbonate or phosgene) with polyols (preferably diols). Examples of such diols include ethylene glycol, 1,2- and 1,3-propylene glycol, 1,3- and 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, neopentyl glycol, 1,4-bis(hydroxymethyl)cyclohexane, 2-methyl-1,3-dipropylene glycol, 2,2,4-trimethylpentanediol, polypropylene glycol, dibutylene glycol, polybutylene glycol, bisphenol and lactone-modified diols. Examples of polycarbonate diols and their preparation can be found in, for example, EP 1359177A.
[0081] Polyether carbonate polyols can be prepared by adding carbon dioxide and an alkylene oxide compound to a starter containing active hydrogen and can also be used in the present invention. Examples of polyether carbonate polyols and their preparation can be found in, for example, EP2910585 A,
[0024] -
[0041] .
[0082] Polymer polyols are polymer-modified polyether polyols, preferably grafted polyether polyols or polyether polyol dispersions. Examples of polymer polyols and their preparation can be found on page 89 in "Kunststoff-Handbuch", Volume VII "Polyurethanes", 3rd edition, Carl Hanser Verlag, Munich / Vienna, 1993, pp. 88-90 and EP 1873 170 A1.
[0083] Polyetherester polyols are polyhydroxy polymers containing ether and polyester groups. They can be prepared, for example, by reacting dicarboxylic acids or their derivatives with polyether polyols (as described herein), or by epoxidation of starting compounds containing ester groups. Examples of polyetheresters and their synthesis are described in WO 2010 / 043624 A and EP 1 923 417 A. Polyetherester polyols can also advantageously be prepared from bio-based sources, for example, from natural oil-based acids, esters, and polyols, as described herein.
[0084] Exemplary representatives of component B2) are also described in “Kunststoff-Handbuch”, Volume VII “Polyurethanes”, 3rd Edition, Carl Hanser Verlag, Munich / Vienna, 1993, pages 57-67.
[0085] Furthermore, the isocyanate-reactive component B) may contain at least one compound B3) selected from components capable of acting as a free-radical polymerization accelerator.
[0086] Reaction accelerators known to those skilled in the art include, for example, transition metal salts (e.g., based on platinum, tin, copper, cobalt, or iron), amino compounds, ammonium salts, and aniline compounds. Most compounds disclosed in the literature are capable of promoting or catalyzing urethane addition polymerization and free radical polymerization. Typically, reaction accelerators for free radical polymerization reactions comprise mixtures of the aforementioned compounds.
[0087] It has been found to be advantageous if the reaction accelerator B3) used in the polyurethane-poly(meth)acrylate reactive composition does not contain catalytically active amines, ammonium salts, or potassium salts. Preferably, the reaction accelerator B3) used in the polyurethane-poly(meth)acrylate reactive composition does not contain either amines, ammonium salts, or potassium salts.
[0088] Preferably, the reaction accelerator B3) comprises a cobalt(II) salt. Particular preference is given to using cobalt(II) carboxylates.
[0089] In a preferred embodiment, the free radical reaction accelerator B3) consists of a cobalt(II) salt, in particular cobalt(II) acetate and / or cobalt(II) ethylhexanoate.
[0090] The polyurethane-poly (meth) acrylate reactive composition further comprises C) a free radical reaction initiator, which can be added to the isocyanate reactive component B), or to the isocyanate component A), or to both. Preferably, before mixing with component B), it is added to the isocyanate component A) to form a premixed component ("premix") of isocyanate A) and free radical reaction initiator C) to avoid premature start of the polymerization reaction in the isocyanate reactive component B). The initiator can be selected from peroxides, peroxyesters, ketone peroxides, diacyl peroxides, peroxyketals, peroxycarbonates, persulfides, peroxyboric acid, azo compounds and / or other suitable free radical initiators capable of initiating the curing of double bond-containing compounds. Examples include tert-butyl peroxyisopropyl carbonate, peroxy 3,5,5-trimethylhexanoate, methyl ethyl ketone peroxide, cumyl hydroperoxide and tert-butyl peroxybenzoate. Peroxyesters preferably have the following structural formula I:
[0091]
[0092] where R 1 and R 2 represents an alkyl group and / or an aryl group.
[0093] Particularly preferred are tert-butyl perbenzoate, tert-amyl perbenzoate and / or tert-amyl peroxyacetate. Tert-butyl perbenzoate is most preferred.
[0094] If a free radical initiator having a peroxyester functionality of the formula (I) is added, its content—meaning the amount of carbonyl peroxy moiety [—(C═O)OO]——is preferably 0.1 to 3% by weight, particularly preferably 0.1 to 2% by weight, based on 100% by weight of the isocyanate-reactive components.
[0095] The addition of 1 to 3% by weight of tert-butyl perbenzoate is particularly advantageous.
[0096] Free radical reaction inhibitors suitable for use in the present invention include polymerization inhibitors, polymerization retardants, etc. Free radical reaction inhibitors include, but are not limited to, some phenols, quinine, or catalytically inactive amine compounds (e.g., hindered amines), examples of which include p-methoxyphenol, benzoquinone, polymethylpiperidine derivatives, etc.
[0097] Free radical reaction promoters suitable for use in the present invention that can improve the reactivity of the initiator and promoter combination include but are not limited to organic ligands such as acetylacetone and catalytically inactive amines such as hindered amines, N,N-dimethylacetoacetamide, N,N-diethylacetoacetamide, etc.
[0098] However, when using the accelerator B3) according to the invention, the addition of reaction accelerators can be avoided, which is an advantage of the polyurethane-poly(meth)acrylate reactive composition according to the invention. Therefore, in a preferred embodiment, the polyurethane-poly(meth)acrylate reactive composition does not contain any free radical reaction accelerators.
[0099] B) may also optionally contain other isocyanate-reactive compounds (=active hydrogen atoms), for example compounds having SH groups and acidic CH groups. Amine groups are permitted only if they are not catalytically active in urethane reactions or free-radical polymerization reactions (e.g., due to steric hindrance). However, even with the presence of such other isocyanate-reactive compounds, more than 90%, in particular more than 95%, especially more than 99%, and very particularly 100%, of all isocyanate-reactive hydrogen atoms in B) are derived from OH groups. Preferably, no isocyanate-reactive components containing amine groups are present in B2.
[0100] In addition to components B1 and B2, B) may optionally comprise compounds containing one or more olefinic functional groups, such as, but not limited to, allyl / aryl (meth)acrylates, ether (meth)acrylates, and crosslinking acrylate and (meth)acrylate monomers containing isocyanate-reactive groups other than hydroxyl groups.
[0101] In addition, the polyurethane-poly(meth)acrylate reactive composition may also contain non-isocyanate reactive compounds, such as compounds containing one or more olefin functional groups, such as but not limited to styrenes, vinyl esters, acrylate and methacrylate monomers, such as but not limited to allyl / aryl (meth)acrylates, ether (meth)acrylates, and cross-linking acrylate and (meth)acrylate monomers with f(olefin)>1.
[0102] The polyurethane-poly(meth)acrylate reactive composition may further comprise other auxiliary agents or additives, as long as they do not comprise catalytically active amines. These other auxiliary agents or additives include, but are not limited to, fillers, internal mold release agents, flame retardants, smoke suppressants, dyes, pigments, antistatic agents, antioxidants, UV stabilizers, diluents, defoamers, coupling agents, surface wetting agents, leveling agents, moisture absorbers, molecular sieves, thixotropic agents, plasticizers, blowing agents, foam stabilizers, foam homogenizers, free radical reaction inhibitors, or combinations thereof, which may optionally be included in the isocyanate component A) and / or the isocyanate-reactive component B), or may be added separately to the polyurethane-poly(meth)acrylate reactive composition during mixing.
[0103] The filler may be selected from aluminum hydroxide, bentonite, fly ash, wollastonite, perlite powder, fly ash floating beads, calcium carbonate, talc, mica powder, china clay, fumed silica, expandable microspheres, diatomaceous earth, volcanic ash, barium sulfate, calcium sulfate, glass microspheres, rock powder, wood powder, sawdust, bamboo powder, bamboo chips, rice grains, chopped crop straw, chopped sorghum straw, graphite powder, metal powder, recycled powder of thermosetting composite materials, plastic particles or powders, or combinations thereof. The glass microspheres may be solid or hollow.
[0104] Internal mold release agents suitable for use in the present invention include any conventional mold release agents used to make polyurethanes, and examples include long-chain carboxylic acids, particularly fatty acids, such as stearic acid; amines of long-chain carboxylic acids, such as stearamide; fatty acid esters; metal salts of long-chain carboxylic acids, such as zinc stearate; or polysiloxanes.
[0105] Examples of flame retardants suitable for use in the present invention include triaryl phosphates, trialkyl phosphates, halogen-containing triaryl phosphates or trialkyl phosphates, melamine, melamine resins, halogenated paraffins, red phosphorus, or combinations thereof.
[0106] Other adjuvants suitable for use in the present invention include dehumidifiers such as molecular sieves, silanes, or oxazolidines; defoamers, degassing agents, and air release agents (e.g., polydimethylsiloxane); and coupling agents such as monoethylene oxide. Coupling agents are particularly preferred for enhancing the bond strength between the resin matrix and the fiber reinforcement. Wetting agents are particularly preferred for improving the fiber wettability of the fiber reinforcement during the impregnation process. Fine fillers such as clay or fumed silica are commonly used as thixotropic agents.
[0107] In order to produce fiber-reinforced polyurethane-poly (meth) acrylate composite material, polyurethane-poly (meth) acrylate reactive composition is mixed with reinforcing material. Suitable reinforcing material comprised in fiber-reinforced polyurethane-poly (meth) acrylate composite waste comprises glass fiber, carbon nanotube, carbon fiber, polyester fiber, natural fiber, aramid fiber, nylon fiber, basalt fiber, boron fiber, silicon carbide fiber, asbestos fiber, whisker, hard particle, metal fiber and combination thereof. Glass fiber is particularly preferred reinforcing material.
[0108] The use of the core material in combination with the polyurethane-poly(meth)acrylate resin matrix and the reinforcing material is beneficial to the molding of the composite material and the weight reduction of the composite material. The core materials commonly used in the art can be used for the polyurethane-poly(meth)acrylate composite material of the present invention, and examples thereof include but are not limited to polystyrene foam, such as Polyester PET foam; polyimide PMI foam; polyvinyl chloride foam; metal foam, such as those available from Mitsubishi Corporation; balsa wood, etc.
[0109] In one embodiment of the present invention, the content of the fiber-reinforced polyurethane-poly(meth)acrylate composite material is preferably 1-90 wt %, more preferably 30-85 wt %, most preferably 50-80 wt %, based on 100 wt % of the polyurethane-poly(meth)acrylate composite material.
[0110] A preferred method for producing the polyurethane-poly(meth)acrylate composite material comprising a polyurethane-poly(meth)acrylate resin matrix and a reinforcement material is the vacuum infusion method known to those skilled in the art, also known as vacuum assisted resin transfer molding (VARTM).
[0111] The VARTM method allows to impregnate reinforcing material with polyurethane-poly (meth) acrylate resin, and the driving force of wherein resin flow is pressure difference.The VARTM method generally comprises manually or uses the metering device mixed part or undegassed resin component that mixing chamber is housed, then by being placed in the resin accumulator under atmospheric pressure and atmosphere, mixed material is transported in the mould, then under the driving of pressure difference, resin flows into the mould that reinforcing material is housed.A preferred method comprises direct VARTM method, wherein most of dissolved gas and the moisture in polyurethane-poly (meth) acrylate resin component are removed under reduced pressure, and then they mix in the mixing chamber of metering device, and the mixing chamber of metering device directly transfers mixed material under the driving of pressure difference in the mould containing reinforcing material, and is not exposed to atmosphere.
[0112] The polyurethane-poly(meth)acrylate reactive composition exhibits high conversion rates in a one-pot reaction. The polyurethane-poly(meth)acrylate reactive composition is suitable for use in vacuum infusion methods to prepare polyurethane-poly(meth)acrylate composite materials. It overcomes the low conversion rates typically seen in the prior art and offers a sufficient, or even longer, pot life, thereby enabling the production of polyurethane-poly(meth)acrylate composite materials suitable for use in applications such as infusing large reinforced structures. The polyurethane-poly(meth)acrylate composite materials prepared by vacuum infusion methods exhibit unique properties, such as a fast cure rate, low heat release, and excellent mechanical properties, including high heat distortion temperature, high tensile strength and flexural strength, high fatigue resistance, high ductility, styrene-free properties, and low shrinkage.
[0113] After a product comprising a fiber-reinforced polyurethane-poly(meth)acrylate composite material (e.g., a wind turbine blade) is produced, it reaches the end of its lifecycle after use. The scrapped product is then recycled. The raw materials for the method of the present invention are provided and introduced for recycling according to step (a).
[0114] Because the fiber-reinforced waste composite material introduced in step (a) is decomposed by pyrolysis in the presence of at least one catalyst in the reactor, it is thus obtained that higher efficiency, higher selectivity are decomposed into the resin contained in the fiber-reinforced waste composite material. The catalyst affects the decomposition reaction of the waste material. Suitable catalyst can reduce the pyrolysis temperature, narrow the product range to the desired product, and minimize coking when necessary. In order to obtain efficient method, it is preferred to use low-cost catalyst. These catalysts can, for example, be naturally occurring materials, such as inorganic salts, refractory oxides, minerals and industrial stone materials, and they can selectively introduce ions by simple ion exchange methods, without the need for complicated synthetic methods. These catalysts are easy to obtain, so the price is relatively low. On the other hand, synthetic catalysts, such as zeolite (such as ZSM-5 type, A type, X type, Y type etc.), are examples of effective but not cheap catalysts, because they must be specially manufactured.
[0115] The raw materials preferably contain at least one catalyst selected from alkaline inorganic materials, more preferably from the natural materials defined above. These inorganic materials may be refractory oxides. Refractory oxides are metal oxides that are stable at high temperatures of 350°C to 700°C. Such oxides used as catalysts include oxides of aluminum, magnesium, zirconium, titanium, chromium, zinc, tin, and other metals, or combinations of aluminum oxide with magnesium oxide and / or calcium oxide.
[0116] Crystalline inorganic materials include aluminosilicates, silicoaluminophosphates, silicalites, spinels and other natural zeolites and clays. Therefore, at least one compound selected from inorganic salts, minerals, metal oxides, mixed oxides, clays and zeolites is particularly suitable for use as the catalyst.
[0117] As particularly preferred suitable catalysts, the raw material comprises at least one basic catalyst or at least one catalyst having Lewis basic sites. If the catalyst is a solid basic catalyst, the number and intensity of the basic sites of the catalyst can be determined by Fourier transform infrared spectroscopy and CO2 temperature programmed desorption (TPD-CO2) or conventional titration.
[0118] Very particularly preferred catalysts comprise at least one aluminum oxide selected from oxides or mixed oxides having a spinel structure, a hydrotalcite structure or a γ-Al 2 O 3 structure.
[0119] More preferred catalysts are selected from mixed oxides of Al2O3 and MgO. Preferred mixed oxides of Al2O3 and MgO have a spinel structure or a hydrotalcite structure.
[0120] According to the present invention, both homogeneous and / or heterogeneous catalysts can be used. However, embodiments of the process of the present invention preferably use heterogeneous catalysts. It has been found that it is advantageous if the catalyst is preferably introduced into the reactor in the form of solid particles (particularly bulk). The average particle size of the solid particles of the heterogeneous catalyst used (particularly loose solid particles in the bulk) is the average diameter X 50,3 (Volume average) is 0.01mm to 5cm, preferably 0.1mm to 5cm. Average particle diameter X 50,3 The particle size can be determined by sieving or using a particle size analyzer Camsizer from Retsch.
[0121] When using a heterogeneous catalyst, it has been found to be particularly suitable in another preferred embodiment if the catalyst particles have a smaller particle size than the particles of the waste composite material. Thus, it is preferred that the average particle size of the catalyst in the pyrolysis material is smaller than the average particle size of the waste composite material.
[0122] The catalyst can be mixed with the packing material or added directly to the packing material. Since the catalyst used in the method of the present invention is prone to accumulate coke and other carbon residues, when using the catalyst, it is preferred to use a reactor with a simple structure and capable of discharging the catalyst and continuously regenerating. Therefore, compared with a fixed bed reactor, it is preferred to use a continuous stirred tank reactor (CSTR), a moving bed reactor, a spiral reactor, a screw conveying reactor, an entrained bed reactor, a rotating cone reactor or a fluidized bed reactor.
[0123] The feedstock introduced into the reactor in step (a) is at least partially decomposed according to step (b) to form a pyrolysis product and a pyrolysis residue.
[0124] A preferred embodiment of the process according to the invention is that the reinforcing material and the catalyst are recovered from the pyrolysis residue according to step (d).
[0125] The catalyst remaining in the pyrolysis residue, including deactivated catalyst (e.g., catalyst deactivated by coking), can be easily separated from the larger glass fibers and fed to a regenerator after the pyrolysis residue is discharged from the reactor. After regeneration, it can be added to the feedstock to be fed to the pyrolysis reactor in step (b), or it can be added separately to the reactor. The most preferred reactor should have a short contact time, thorough mixing of the feedstock components, and continuous circulation of the regenerated catalyst in the pyrolysis zone. Screw reactors, rotary kilns, or fluidized bed reactors are particularly preferred due to their aforementioned characteristics.
[0126] Since both the catalyst and the recovered reinforcement material (i.e., from the fiber-reinforced polyurethane-poly(meth)acrylate composite waste) remain in the pyrolysis residue, the recovery and separation of these two components is a preferred embodiment of the method according to the invention. The recovery and separation can be carried out, for example, by sieving, wherein the reinforcement material remains on the sieve as a sieving residue, while the catalyst, as a smaller component, is separated as a sieving product and is ready for the above-mentioned regeneration.
[0127] The decomposition in step (b) of the process according to the invention is carried out within a certain temperature range in the presence of reduced amounts of oxygen or even in the absence of oxygen.
[0128] After the feedstock is introduced into the reactor, it is heated to a temperature of 350° C. to 700° C. As one embodiment of the process, the results of the process according to the invention can be improved particularly successfully if the introduced feedstock is tempered to a temperature of 350° C. to 700° C. and, after reaching this target temperature, the feedstock is tempered accordingly until the resulting pyrolysis residue is discharged for a residence time of 1 second to 2 hours, preferably 2 minutes to 60 minutes, during which the temperature and oxygen content in the reactor are at the values defined in step (b).
[0129] In addition, good results can be achieved if the pyrolysate is discharged from the reactor in step (b) by guiding a gas flow through the reactor or by suction, and further preferably, the residence time of the pyrolysate (the period between the time of introducing the raw materials into the reactor in step (a) and the time of discharging the pyrolysate) is 0.1 to 10 seconds, preferably 0.5 to 5 seconds, and particularly preferably 0.5 to 2 seconds.
[0130] If a gas stream is passed through the reactor for this purpose, suitable gases for this gas stream are in particular inert gases, preferably selected from nitrogen, argon, CO2, NO or mixtures thereof.
[0131] If an air flow is used to discharge the pyrolyzate, according to a preferred embodiment of the present method, the flow rate of the air flow in the preferred reactor (in terms of superficial velocity) is 0.01 m / s to 20 m / s. If a fixed bed reactor is selected as the reactor, according to the present invention, the flow rate of the air flow in the preferred reactor (in terms of superficial velocity) is 0.03 m / s to 1 m / s. If a fluidized bed reactor is selected as the reactor, according to the present invention, the flow rate of the air flow in the preferred reactor (in terms of superficial velocity) is 0.5 m / s to 2 m / s. If an entrained bed reactor is selected as the reactor, according to the present invention, the flow rate of the air flow in the preferred reactor (in terms of superficial velocity) is 5 m / s to 20 m / s.
[0132] As decomposition conditions for the pyrolysis in step (b) according to the present invention, the temperature in the reactor is 350 to 700° C., and the amount of oxygen in the reactor is 0 to 2.0% by volume based on the total volume of the gas in the reactor.
[0133] According to the present invention, in order to adjust the amount of oxygen, an inert gas, in particular nitrogen, argon, CO2, NO, or a mixture thereof, is introduced into the reactor containing the raw materials. In addition to oxygen, various reactive gases may be added to the inert gas, in particular selected from methane, gaseous H2O, hydrogen, or a mixture thereof.
[0134] In order to minimize the introduction of oxygen into the raw materials when they are introduced into the reactor, oxygen may be removed from the raw materials before they are introduced into step (a), for example, by stripping them with a stripping gas in a receiving tank upstream of the reactor. For example, an inert gas (particularly nitrogen, argon, CO2, NO, and mixtures thereof) may be introduced as a stripping gas from above or below (preferably from above) the receiving tank through a glass frit into the raw materials in the container to remove oxygen.
[0135] In a preferred embodiment of the process according to the present invention, the temperature in step (b) is from 350°C to 650°C, preferably from 400°C to 580°C, more preferably from 450°C to 550°C.
[0136] In a further preferred embodiment of the process according to the invention, the amount of oxygen in the reactor in step (b) is at most 0.5% by volume, preferably at most 0.1% by volume, based in each case on the total volume of the gas present in the reactor.
[0137] In a very preferred embodiment of the process according to the invention, in step (b), firstly, the temperature is from 350° C. to 650° C., preferably from 400° C. to 580° C., more preferably from 450° C. to 550° C., and secondly, the amount of oxygen in the reactor is at most 0.5% by volume, preferably at most 0.1% by volume, based in each case on the total volume of the gas present in the reactor.
[0138] According to a preferred embodiment of the process, the total pressure according to step (b) is at most 1.2 bar.
[0139] According to another preferred embodiment of the process, the total pressure according to step (b) is at least 0.8 bar.
[0140] A preferred embodiment of the process is a continuous process. For this purpose, at least steps (a) and (b) are carried out simultaneously.
[0141] The pyrolysis product obtained according to step (c) can be worked up by standard separation methods to obtain at least one organic amine compound.
[0142] According to a preferred embodiment of the present invention, at least one recovered organic amine compound comprises at least two amino groups and is selected from the group consisting of:
[0143]
[0144] Here, n is a number from 0 to 8, preferably from 0 to 4, particularly preferably from 0 to 2.
[0145] It is particularly preferred if the pyrolysis product comprises (i) at least one aromatic organic compound having at least two amino groups and / or (ii) at least one aromatic organic compound having one amino group.
[0146] According to a preferred embodiment of the present invention, the recovered organic amine compound comprises at least one aromatic organic compound containing one amino group, which is selected from aniline, toluidine or a mixture thereof.
[0147] Another aspect of the present invention is a mixture of fiber-reinforced polyurethane-poly(meth)acrylate composite waste and a catalyst for use in a pyrolysis reactor. Thus, this aspect is defined as a composition comprising a mixture of at least one fiber-reinforced polyurethane-poly(meth)acrylate composite waste and at least one catalyst capable of influencing the thermal decomposition of the waste.
[0148] The fiber-reinforced polyurethane-poly(meth)acrylate composite material of the waste material is obtained from at least one reinforcing material and at least one polyurethane-poly(meth)acrylate reactive composition, wherein the polyurethane-poly(meth)acrylate reactive composition comprises:
[0149] A) an isocyanate component comprising one or more organic polyisocyanates;
[0150] B) an isocyanate-reactive component comprising:
[0151] B1) one or more (meth)acrylate monomers containing at least one hydroxyl functional group;
[0152] B2) one or more organic polyols;
[0153] C) a free radical reaction initiator, and
[0154] The polyurethane-poly(meth)acrylate resin is obtained by reacting the components, preferably by a one-pot process.
[0155] The composition is preferably used as a raw material component of the process of the present invention. Therefore, another aspect of the present invention is the use of the composition in the pyrolysis of fiber-reinforced polyurethane-poly(meth)acrylate composite waste, preferably by the above-described process of the present invention.
[0156] All preferred embodiments of the fiber-reinforced polyurethane-poly(meth)acrylate composite waste and catalyst defined in the above method of the present invention are also preferred embodiments of their compositions and uses. Example
[0157] To prepare the experiments for the wind turbine blade composite material, the reactor was first filled. The particles used as the scrap composite material according to the invention comprised approximately 73% by weight of glass fibers and 27% by weight of resin. The resin was prepared from 100 parts by weight of an isocyanate-reactive material (B), which comprised 55% by weight of a polyol (B2) and 45% by weight of hydroxypropyl methacrylate (HPMA) (B1), relative to the weight of component (B), and 88 parts by weight of an isocyanate (A). The free radical initiator used was tert-butyl peroxybenzoate. The catalyst was prepared (purchased from Sasol). A mixture of SBA200 and composite particles was prepared and loaded into the reactor from below. After the reactor was filled, the terminal pipe was isolated. A cooling trap was then prepared and connected to the reactor. Thermocouples were connected between the reactor and the cooling trap.
[0158] The temperature was set to 490°C.
[0159] The temperature was then raised for 20 minutes. The experiment lasted for 30 minutes. Then, nitrogen was purged into the reactor for another 10 minutes.
[0160] After the experiment, the liquid nitrogen below the cold trap was removed.
[0161] After the cold trap thaws, flush the pyrolysis oil from the cold trap with 25 ml of methanol. Pour the pyrolysis oil in methanol into a prepared sample glass containing cumene (internal standard for gas chromatography). After the reactor cools, flush the terminal tubing and perforated plate insert with 25 ml of methanol into another glass containing cumene (internal standard).
[0162] GC analysis was performed on the cold trap and reactor samples using 100 μL of cumene per 25 mL of sample solution and pyrolysis oil.
[0163] Analyses were performed using an Agilent Technologies 7890A GC system. A Restek Rxi-1ms GC column was used to separate the substances within the system. The column used was 30 m long with an inner diameter of 0.32 mm. The column temperature was adjusted from -60°C to 330 / 350°C.
[0164] Evaluation of GC data by software (from Thermo Fisher Scientific).
[0165] result:
[0166] The compositions determined according to the above analysis are summarized in Table 1 below.
[0167] Table 1: Composition of the pyrolysis products and pyrolysis residues of fiber-reinforced composite waste particles measured at 273°C [wt%]:
[0168]
[0169] The residual amount of components produced by pyrolysis was either considered gaseous at ambient temperature and therefore not detectable by the above procedure, or was considered liquid but could not be detected due to the large difference in the setup compared to the oil fraction obtained.
Claims
1. A method for pyrolysis of waste fiber reinforced polyurethane-poly (meth) acrylate composite materials, comprising at least the following steps: (a) introducing a feedstock comprising at least one fiber-reinforced polyurethane-poly(meth)acrylate composite waste material into a reactor, The fiber-reinforced polyurethane-poly(meth)acrylate composite material in the waste is obtained from at least one reinforcing material and at least one polyurethane-poly(meth)acrylate reactive composition, wherein the polyurethane-poly(meth)acrylate reactive composition comprises: A) an isocyanate component comprising one or more organic polyisocyanates; B) an isocyanate-reactive component comprising: B1) one or more (meth)acrylate monomers containing at least one hydroxyl functional group; B2) one or more organic polyols; C) a free radical reaction initiator, and wherein the polyurethane-poly(meth)acrylate resin is obtained by reacting the components, preferably by a one-pot process; and (b) decomposing the polyurethane-poly(meth)acrylate resin in the introduced fiber-reinforced polyurethane-poly(meth)acrylate composite waste at a temperature of 350° C. to 700° C. in the presence of a catalyst capable of affecting thermal decomposition of the waste, to obtain at least a gaseous pyrolysis product and a pyrolysis residue, the pyrolysis residue containing at least separated reinforcement material as a solid, wherein (i) during the decomposition process, the amount of oxygen in the reactor is at most 2.0% by volume of the total volume of the gas phase in the reactor, and (ii) during said decomposition process, removing the pyrolysate from the reactor, and (iii) removing the pyrolysis residue from the reactor; and (c) cooling the removed pyrolysate to below 350° C. to obtain a pyrolysate selected from a pyrolysate condensate, a sublimed pyrolysate, or a mixture thereof; and (d) preferably recovering the reinforcing material and catalyst from the pyrolysis residue.
2. The method according to claim 1, characterized in that The reinforcing material of the fiber-reinforced polyurethane-poly(meth)acrylate composite waste is selected from glass fiber, carbon nanotube, carbon fiber, polyester fiber, natural fiber, aramid fiber, nylon fiber, basalt fiber, boron fiber, silicon carbide fiber, asbestos fiber, whisker, hard particles, metal fiber or a combination thereof.
3. The method according to claim 1, wherein The fiber-reinforced polyurethane-poly(meth)acrylate composite waste contains the reinforcing material in an amount of 30-85 wt %, preferably 50-80 wt %, based on the total weight of the fiber-reinforced polyurethane-poly(meth)acrylate composite waste.
4. The method according to claim 1, wherein The decomposition is carried out at a temperature of 350°C to 650°C, preferably 400°C to 580°C, most preferably 450°C to 550°C.
5. The method according to claim 1, wherein During the decomposition in step (b), the amount of oxygen in the reactor is at most 0.5% by volume, preferably at most 0.1% by volume, based on the total volume of the gas phase in the reactor.
6. The method according to claim 1, wherein During step (b), an inert gas is passed through the reactor, preferably nitrogen, argon, CO2, NO or a mixture thereof.
7. The method according to claim 1, wherein The component A) is at least one compound selected from aliphatic diisocyanates, aliphatic polyisocyanates, alicyclic diisocyanates, alicyclic polyisocyanates, aromatic diisocyanates, and aromatic polyisocyanates.
8. The method according to any one of the preceding claims, characterized in that The component A) comprises at least one compound selected from the group consisting of 1,4-butylene diisocyanate, 1,5-pentylene diisocyanate, 1,6-hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, bis(4,4'-isocyanatocyclohexyl)methane, 1,4-cyclohexyl diisocyanate, 1,4-phenylenediisocyanate, 2,4-toluene diisocyanate, 2,6-methanesulfonate, 1,4-diisocyanato- ... Phenylene diisocyanate (TDI), 1,5-naphthalene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate (monomeric MDI, mMDI), polyphenylene polymethylene polyisocyanate (pMDI), 1,3-bis-(2-isocyanato-propan-2-yl)-benzene, 1,4-bis-(2-isocyanato-propan-2-yl)-benzene (TMXDI), 1,3-bis-(isocyanatomethyl)benzene (XDI).
9. The method according to claim 1, wherein The component B1) comprises at least one hydroxy(meth)acrylate monomer having a hydroxyl number of 150-700 mg KOH / g, more preferably 220-600 mg KOH / g, most preferably 300-500 mg KOH / g.
10. The method according to any one of the preceding claims, characterized in that The component B1) comprises at least one compound selected from hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate and hydroxybutyl (meth)acrylate.
11. The method according to claim 1, wherein The component B2) comprises at least one compound selected from polyether polyols, polyester polyols, polyether ester polyols, polymer polyols, polycarbonate polyols, and polyether carbonate polyols, preferably at least one compound selected from polyhydroxy polyethers.
12. The method according to any one of the preceding claims, characterized in that The component C) comprises at least one compound selected from the group consisting of peroxides, peroxyesters, ketone peroxides, diacyl peroxides, peroxyketals, peroxycarbonates, persulfides, peroxyboric acid, and azo compounds.
13. The method according to any one of the preceding claims, characterized in that The catalyst is at least one compound selected from inorganic salts, minerals, metal oxides, mixed oxides, clays, zeolites or mixtures thereof.
14. The method according to any one of the preceding claims, characterized in that The catalyst is selected from at least one mixed oxide of Al2O3 and MgO.
15. The method according to any one of the preceding claims, characterized in that At least during the decomposition according to step (b), water vapor is introduced into the reactor.
16. The method according to any one of the preceding claims, characterized in that The reinforcing material is recovered from the pyrolysis residue by sieving.
17. The method according to any one of the preceding claims, characterized in that The catalyst is recovered from the pyrolysis residue by sieving.
18. A composition comprising a mixture of at least one fiber-reinforced polyurethane-poly(meth)acrylate composite waste material and at least one catalyst capable of affecting the thermal decomposition of said waste material, The fiber-reinforced polyurethane-poly(meth)acrylate composite material in the waste is obtained from at least one reinforcing material and at least one polyurethane-poly(meth)acrylate reactive composition by a one-pot process, wherein the polyurethane-poly(meth)acrylate reactive composition comprises: A) an isocyanate component comprising one or more organic polyisocyanates; B) an isocyanate-reactive component comprising: B1) one or more (meth)acrylate monomers containing at least one hydroxyl functional group; B2) one or more organic polyols; C) a free radical reaction initiator, and The polyurethane-poly(meth)acrylate resin is obtained by reacting the components.
19. Use of the composition of claim 18 in the pyrolysis of waste fiber-reinforced polyurethane-poly(meth)acrylate composites, preferably by the process according to any one of claims 1 to 17.
Citation Information
Patent Citations
Preparation and use of high molecular aliphatic polycarbonates
EP1359177A1
Method for stripping polymer polyols
EP1873170A1
Process for the preparation of polyether-ester polyols
EP1923417A1
Polyurethane composite material and process of preparing same
EP3129422B1
Terephthalic acid-based polyester polyols
WO2010043624A2